The Quality of Voter Participation in the 2024 Kupang City Regional Election A Case Study of Gen Z Voters and Elderly Voters - Lakabela, Pascaliani Estyka; Sayrani, Laurensius P.; Rohi , Rudi (PT Keberlanjutan Strategis Indonesia, 2026)
Voter participation is a key indicator of democratic quality in regional elections. This study analyzes the quality of voter participation in the 2024 Kupang City Regional Election by focusing on two voter groups: Generation Z voters and elderly voters. Using a qualitative phenomenological approach, this research explores the experiences, motivations, obstacles, and political behavior dynamics of both groups. Data were collected through in-depth interviews with 14 informants, consisting of the Chairperson of the Kupang City General Elections Commission (KPU), KPU secretariat staff, six Gen Z voters, and six elderly voters, supported by documentation studies and official KPU data. The findings show that Gen Z voter participation is largely influenced by rational considerations and access to digital information; however, political awareness and consistent voter turnout remain relatively weak. In contrast, elderly voters demonstrate more stable participation driven by emotional attachment, life experience, and social proximity to candidates. Supporting factors include political education initiatives by the KPU, social media campaigns, and accessible election information. Meanwhile, inhibiting factors involve technical and administrative issues, such as reduced polling stations, negative political perceptions, voter fatigue due to closely timed elections, and the prevalence of transactional politics. This study concludes that voter participation quality in the 2024 Kupang City Regional Election still faces substantial challenges and requires more adaptive outreach strategies, improved election governance, and strengthened political literacy, particularly among younger voters.